Homotypic Targeting Delivery of siRNA with Artificial Cancer Cells. Issue 9 (17th March 2020) - Zhang, Lingmin; Deng, Sai; Zhang, Yanfen; Peng, Qingsheng; Li, Huan; Wang, Ping; Fu, Xiaomei; Lei, Xueping; Qin, Aiping; Yu, Xiyong
Abstract: The camouflage with cell membrane bestows nanoparticles with cell‐like functions, such as specific recognition, long blood circulation, and immune escaping. For cancer therapy, the nanoparticles camouflaged with cancer cell membrane (CCM) from homologous cells show homotypic targeting delivery of small molecule compounds, photosensitizers, or enzymes to the tumors. However, effective gene therapy encounters difficulties by this approach due to the properties of nucleic acids. Herein, a cancer cell‐like gene delivery system is developed using an excellent polymer poly(β‐amino ester) (PBAE) to condense small interfering RNA (siRNA) (targeting to Plk1 gene) into nanoparticles (PBAE/siPlk1) as the core, which is further camouflaged with CCM. These novel biomimetic nanoparticles CCM/PBAE/siPlk1 (CCMPP) demonstrate highly specific targeting to homotypic cancer cells, effective downregulation of PLK1 level, and inducing apoptosis of cancer cells. Based on the homotypic binding adhesion molecules on the CCM, the cellular internalization and homotypic‐targeting accumulation to the tumors are clearly improved. CCMPP induces highly efficient apoptosis of cancer cells both in vitro and in vivo and results in significant tumor inhibition. The artificial cancer cells with homotypic properties can serve as a biomimetic delivery system for cancer‐targeted gene therapy. Abstract : A novel style of artificial cancer cells is constructed for small interfering RNA (siRNA) delivery, by virtue of poly(β‐amino ester) (PBAE) clustering siRNA as core and camouflage with homotypic cancer cell membranes. The nanoparticles show highly specific homologous targeting and efficient cellular uptake. Efficient gene silence is achieved, leading to effective apoptosis and proliferation inhibition both in vitro and in vivo.